An improved quantum condition for the bound state problem in non-relativistic quantum mechanics using the NUFA method. - Rajesh Kumar, P. (EDP Sciences, Società Italiana di Fisica and Springer Berlin Heidelberg, 2022)
The bound state is an intriguing quantum mechanics problem. In this paper, an improved and elegant quantum condition for the bound state problem in non-relativistic quantum mechanics using the Nikiforov-Uvarov functional analysis (NUFA) method is presented. From the quantum condition, two simple formulas are obtained to calculate the energy spectrum for the bound state problem, one for the case when the parameter α3≠0 and the other when α3→0. The corresponding eigenstates are also derived in terms of hypergeometric functions. Two bound state problems are studied using the improved quantum condition. (Abstract by author)